Randomized comparative study of safety and efficacy of oral and vaginal misoprostol in the termination of second trimester pregnancy at tertiary care institution - S., Lujimmala; E., Anitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: A prospective randomized study was conducted in 72 pregnant women, with gestational period between 12 and 20 weeks, to compare the efficacy and safety of oral versus vaginal administration of misoprostol for second trimester pregnancy termination. The study was conducted in the Department of Obstetrics and Gynaecology, Government Kilpauk Medical College and Hospital (KMCH), Chennai, South India from November 2012 and November 2013. Methods: Women aged 18-38 years requesting MTP for maternal reason, foetal congenital anomalies and intrauterine foetal demise were randomly assigned into two groups. Group A (n=36) had misoprostol orally while the Group B (n=36) received misoprostol by vaginal route. Dosage regimen was similar in both the groups that was 200µg every 4 hrs until the abortion occurred, maximum up to 6 doses. Efficacy included induction to delivery interval and safety included maternal complications and side-effects like nausea, vomiting, diarrhoea, fever and abdominal pain and results were compared. Results: The percentage of women who delivered was significantly higher in the vaginal group than the oral group (94.44% versus 66.67%, P <0.03018) within 24 hours. The induction to delivery interval and incidence of side-effects were noted. Conclusions: Vaginal administration of misoprostol resulted in a higher success rate and misoprostol is safe and effective drug for second trimester pregnancy termination.